Patients’ Knowledge and Pharmacists’ Practice Regarding the Long-Term Side Effects of Proton Pump Inhibitors; a Cross-sectional Study - Alblooshi, Aisha Juma; Mirza R. Baig; S. Anbar, Hanan (Archives of Academic Emergency Medicine, 2024)
Introduction: Proton pump inhibitors (PPI) are a commonly prescribed medication, but recent evidence suggests that their long-term use may lead to several adverse events. To address this issue, our study aims to assess patient awareness and pharmacist practices in educating patients about the potential risks associated with prolonged PPI use. Methods: Two questionnaires were developed by researchers and administered in the United Arab Emirates from June to August 2021 to gather insights from patients and pharmacists about the use of PPIs, their knowledge of potential side effects, and their experiences and attitudes toward receiving education about PPI side effects. The patients' knowledge was evaluated based on their cumulative correct answers to questions related to PPI’s long-term adverse effects including increased fracture risk and hypocalcemia, vitamin B12 deficiency, hypomagnesemia, and the caution of abrupt withdrawal. All statistical analyses were conducted using SPSS 25.0 software. Results: Overall, 348 participants with a median age of 40 years participated in the survey, among them, 91 (26.14%) used various forms of PPI with 38% of users taking PPI as over-the-counter drugs. Patients had low knowledge about PPI side effects and their proper discontinuation with a median knowledge score of 0 (Interquartile range: 0-2) and only 22.2% of patients were familiar with at least three out of five asked harms. Those with lower knowledge were more likely to be Emirati compared to other nations (p=0.004) and aged over 30 years compared to their younger counterparts (p = 0.016). Few patients have obtained the relevant information from their physicians (25%) or pharmacists (7%). Inquiring 136 pharmacists, it was shown that the most common education was concerning vitamin B12 deficiency (62.5%) followed by fracture risk (58.09%) yet less than half (48%) of pharmacists instructed patients about the potential risk of hypomagnesemia. Almost all pharmacists (99%) agreed that there is a requirement for additional education on the possible harmful consequences of PPIs. Conclusion: The present study has established that a considerable proportion of PPI users in the UAE lack the necessary awareness about the potential adverse effects of PPI despite their extensive use in this country. The current pharmacist practice is inefficient for inculcating the potential harms of chronic PPI use and they are required to optimize their efforts to educate patients and bridge the knowledge gaps.